2008
DOI: 10.1017/s1049096508080815
|View full text |Cite
|
Sign up to set email alerts
|

Teaching with Lecture or Debate? Testing the Effectiveness of Traditional versus Active Learning Methods of Instruction

Abstract: Lecture is, arguably, the oldest known instructional technique used in the university setting.Since it was first employed in Plato's Academy, lecture has become an indispensable part of teaching favored across the college and university curriculum. Recently, this time-honored method of instruction has come under attack for its presumed inability to foster higher order cognitive and attitudinal goals (Cashin 1985;Day 1980;Frederick 1999;Renner 1993). Critics of traditional lecture-based formats call for their r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
75
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(84 citation statements)
references
References 9 publications
7
75
0
2
Order By: Relevance
“…The experimental study of Omelicheva and Avdeyeva (2008) demonstrated that the debate format, compared with lecture, better facilitated students' higher-order cognitive skills of application and critical evaluation. In the same vein, Goodwin (2003) introduced debate in his communication class and students reported gains in developing divergent perspectives on course topics.…”
Section: Debatementioning
confidence: 99%
“…The experimental study of Omelicheva and Avdeyeva (2008) demonstrated that the debate format, compared with lecture, better facilitated students' higher-order cognitive skills of application and critical evaluation. In the same vein, Goodwin (2003) introduced debate in his communication class and students reported gains in developing divergent perspectives on course topics.…”
Section: Debatementioning
confidence: 99%
“…This limited use may relate to the criticisms levied against the Socratic debate method, for being too adversarial and combative. Yet, research has indicated the effectiveness of debates in supporting learning in a variety of disciplines including economics, education, history, marketing, medicine, nursing, psychology, sociology and social work (Dundes, 2001;Helenius et al, 2006;Kennedy, 2009;Omelicheva & Avdeyeva, 2008). There is, however, a significant dearth of literature specifically reflecting on the use of debates in teaching geography, despite the range of topics in the discipline which offer potential for such a method.…”
Section: Debates Within Teachingmentioning
confidence: 99%
“…Furthermore, the literature tends to focus on students' learning outcomes rather than students' responses to active learning. Two exceptions are Omelicheva and Avdeyeva (2008) and Huerta (2007) who describe the challenging task of implementing active learning strategies in large lecture environments. Omelicheva and Avdeyeva present debates as one method of active learning to generate a more engaging learning environment.…”
Section: Active Learning and The Inverted Classroom Model In Politicamentioning
confidence: 99%